2001
DOI: 10.1159/000056341
|View full text |Cite
|
Sign up to set email alerts
|

EEMCO Guidance for the Assessment of Transepidermal Water Loss in Cosmetic Sciences

Abstract: Measurement of transepidermal water loss (TEWL), based on the estimation of the water vapour gradient in an open chamber, is being used to support claims of cosmetics including product mildness, reduction in irritative skin reactions, skin hydration, skin repair, protective effect against UV damage and others. TEWL measurement can also screen ingredients that have a beneficial effect on the barrier function and offer the possibility to monitor in vivo, on human skin, the effect of topical treatment in an objec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
460
1
17

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 462 publications
(486 citation statements)
references
References 62 publications
8
460
1
17
Order By: Relevance
“…12) Recently, it has been reported that skin barrier function in hairless mice is improved by intake of extracts of food materials containing glucosylceramide; the purity was > 6%. 13) It has also been reported that oral intake of glucosylceramide reduced transepidermal water loss (TEWL) 14) in normal adult 12) or in AD patients. 15,16) A. konjac, a rich source of glucocylceramide, has been eaten as food for a long time in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…12) Recently, it has been reported that skin barrier function in hairless mice is improved by intake of extracts of food materials containing glucosylceramide; the purity was > 6%. 13) It has also been reported that oral intake of glucosylceramide reduced transepidermal water loss (TEWL) 14) in normal adult 12) or in AD patients. 15,16) A. konjac, a rich source of glucocylceramide, has been eaten as food for a long time in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, the SC capacitance was measured using a Corneometer®CM (Courage & Khazaka), according to previously reported specifications. 14,15 Measurements were performed on subjects' skin of the inner thigh, buttock, and inner upper arm. Crying infants were not measured until they became quiet or fell asleep.…”
Section: Methodsmentioning
confidence: 99%
“…The amount of water evaporated through the skin can be measured and used for characterizing the epidermal barrier function. If the dermal barrier is damaged, more water can evaporate on the skin than in the case of an intact barrier [12][13][14][15]. TEWL measurements are performed using a small, highly sensitive electrode system, through which the water vapour separated through the skin is led.…”
Section: Biophotonicsmentioning
confidence: 99%
“…The measurements had always been taken on the same skin site for a period of 20 s and stopped when the standard deviation was less than 0.15 g m À2 h À1 . The measurements were carried out in accordance with the published guidelines [13,15].…”
Section: Determination Of Transepidermal Water Loss Values (Tewl)mentioning
confidence: 99%